Failure to disrupt : why technology alone can't transform education - Reich, Justin, 1977- (Cambridge, Massachusetts : Harvard University Press, 2020)
"From MOOCs to autograders to computerized tutors, technologies designed for large-scale learning have never lived up to the hype. Justin Reich once promoted these "transformative" novelties; now he reveals their failures. Successful education reform, he concludes, will focus on incremental institutional change, not the next killer app"
Introduction: Education technology's unrequited disruption -- Part I. Three genres of learning at scale. Instructor-guided learning at scale: massive open online courses -- Algorithm-guided learning at scale: adaptive tutors and computer-assisted instruction -- Peer-guided learning at scale: networked learning communities -- Testing the genres at scale: learning games -- Part II. Dilemmas in learning at scale. The curse of the familiar -- The Edtech Matthew effect -- The trap of routine assessment -- The toxic power of data and experiments -- Conclusion: Preparing for the next learning-at-scale hype cycle.
Includes bibliographical references and index.
Keywords: Educational technology; Educational change; Computer-assisted instruction -- Evaluation; Internet in education -- Evaluation; MOOCs (Web-based instruction) -- Evaluation